The ethnobotanical domain of the Swat Valley, Pakistan - Kishwar Ali; Nasrullah Khan; Inayat-Ur Rahman; Waqar Khan; Murad Ali; Nisar Uddin; Mohammad Nisar (BMC, 2018)
Abstract Background This study contributes to the current ethnomedicinal knowledge of the Swat Valley, Pakistan. District Swat possesses remarkable biodiversity owing to its varied topographical and climatic conditions, prompting a distinct human-plant association. Our hypothesis is that the presence of such a great biodiversity has shaped into a formal ethnobotanical culture in the area transmitted through generations. We suspect that the versatility of some plant species has greater influence on the culture. Therefore, the prime objective of the study is to understand this unique human-plant relationship in the valley and to create scientific roots for the selection and practice of herbs in the ethnobotanical domain of the district. Methods Primary data were collected using questionnaires and face-to-face interviews with the locals. The data collected were used for calculating some important indices, i.e. relative frequency of citation (RFC), participant agreement ratio (PAR), frequency of citation (FC), Smith's Salience Index (SI), Relative Importance Index (RII), Cultural Value Index (CVI) and a newly proposed, Ali's Conservation Priority Index (CPI). Index scores were used as key identifier of the ethnobotanically important plants of the area. Results Residents of the Swat Valley have listed plant uses in 15 use categories. Around 9% of the respondents have a common consensus on the selection and use of plants for the treatment of evil eye with similar results for body cuts (8.2%) followed by psychological/neural ailments (8.0%). Respondents agree that Berberis lyceum Royle. dominates in all five indices. Skimmia laureola Franch. also constitutes one of the central plants of the ethnobotanical domain, ranking second in the SI, fifth in the RII, seventh in CVI, and third in the Cultural Importance Index. It holds the thirty-fifth position in the CPI. Over 80% of the population treat different diseases with herbal remedies. In the common ethnobotanical domain of the area, plants like Mentha longifolia L., Berberis lyceum, and Skimmia laureola are very important and have high salience and importance values, thus suggesting these plants are versatile for their uses in the study area. Conclusion In conclusion, only some plant species are prioritised for their use in the ethnobotanical domain of the community. Medicinal and aromatic plant (MAP) usage is widespread in the Swat Valley. The ethnobotanical knowledge could be used as a tool to understand the adaptability of a specific taxon in the area and the possible conservation risk to their existence.